2018
DOI: 10.1016/j.ebiom.2018.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influence of Toll-like receptors on non-HIV cryptococcal meningitis: An observational cohort study

Abstract: BackgroundCryptococcal meningitis (CM) is a significant source of mortality, the pathogenesis of which has not been fully understood, especially in non-HIV infected populations. We aimed to explore the potential genetic influence of Toll-like receptor (TLR) on non-HIV CM.MethodsThis observational cohort study was done in two stages: a discovery stage and a validation stage. A case-control genetic association study was conducted between 159 non-HIV CM patients and 468 healthy controls. TLR SNPs significantly re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In contrast to other countries, where CM is often diagnosed in patients with HIV or immunocompromised patients, in China, a high proportion of cryptococcosis was reported in immunocompetent persons (34). Jiang et al reported on 159 HIV-negative patients with CM, of whom 85 were normal hosts; however, whether these persons were immunocompetent is unknown, because several genetic predisposition factors for CM have been found in the ethnic Chinese population (46). Most large-scale studies have been conducted in adults; few were dedicated to pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to other countries, where CM is often diagnosed in patients with HIV or immunocompromised patients, in China, a high proportion of cryptococcosis was reported in immunocompetent persons (34). Jiang et al reported on 159 HIV-negative patients with CM, of whom 85 were normal hosts; however, whether these persons were immunocompetent is unknown, because several genetic predisposition factors for CM have been found in the ethnic Chinese population (46). Most large-scale studies have been conducted in adults; few were dedicated to pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 belongs to Th2-type anti-inflammatory cytokine, acts in highly coordinated cytokine network and interferes with innate and adaptive protective immunity in infectious diseases. [ 25 , 26 ] IL-10 also interferes with the balance of Th1/Th2 cells, negatively regulates the response of Th1 lymphocytes, and prevents immunologic injury caused by exacerbated immune responses. [ 27 ] It is believed that ∼50% to 70% of the observed variation in IL-10 production contributes to genetic factors, mainly the polymorphisms in the promoter region of IL-10 gene, those were rs1800896, rs1800871, and 1800872.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of EBioMedicine , Jiang and colleagues report on the association of genetic variants in Toll-like receptors (TLRs) and the risk of non-HIV cryptococcal meningitis (CM) [ 1 ]. CM represents a major cause of morbidity and mortality in HIV-infected patients, especially in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…These receptors have been vastly implicated in anti-cryptococcal immunity [ 5 ], however the question remains as to which TLR-ligand interaction is actually required for the recognition, phagocytosis, and subsequent fungal killing. In this study, Jiang and colleagues provide both genetic and immunological evidence highlighting the pivotal role of TLR-dependent mechanisms of cryptococcal recognition and cytokine production in defining susceptibility to human CM in HIV-uninfected individuals [ 1 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation